2021
DOI: 10.1007/s11625-021-01052-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Malaysian palm oil on sustainable development goals: co-benefits and trade-offs across mitigation strategies

Abstract: Palm oil (PO) is an important source of livelihood, but unsustainable practices and widespread consumption may threaten human and planetary health. We reviewed 234 articles and summarized evidence on the impact of PO on health, social and economic aspects, environment, and biodiversity in the Malaysian context, and discuss mitigation strategies based on the sustainable development goals (SDGs). The evidence on health impact of PO is equivocal, with knowledge gaps on whether moderate consumption elevates risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 183 publications
(220 reference statements)
0
7
0
Order By: Relevance
“…In comparison to the Malaysian context, Naidu and Moorthy [51] showed that the palm oil industry is still able to support the achievement of SDGs such as alleviating hunger (SDG 2), improving health (SDG 3), developing renewable energy (SDG 7), and sustainable consumption and production (SDG 12). Hanafiah et al [52] analyzed that the palm oil industry in Malaysia is considered to bring benefits to achieving economic growth (shown in SDGs 9 and 12), poverty alleviation (SDGs 1, 8, and 10), increased food security (SDGS 2), alternative energy (SDG 9), and enhanced opportunities for work (SDG 1). However, there are some issues in human rights and inequality (SDG 8), greenhouse gas emissions (SDG 13), microclimate and soil nutrient changes (SDGs 6 and 13), sedimentation and hydrological changes (SDG 6), and human conflict with wildlife, invasive species, and reduced biodiversity (SDGs 14 and 15).…”
Section: Rspo Certification Contribution To Sdgs Achievementmentioning
confidence: 99%
“…In comparison to the Malaysian context, Naidu and Moorthy [51] showed that the palm oil industry is still able to support the achievement of SDGs such as alleviating hunger (SDG 2), improving health (SDG 3), developing renewable energy (SDG 7), and sustainable consumption and production (SDG 12). Hanafiah et al [52] analyzed that the palm oil industry in Malaysia is considered to bring benefits to achieving economic growth (shown in SDGs 9 and 12), poverty alleviation (SDGs 1, 8, and 10), increased food security (SDGS 2), alternative energy (SDG 9), and enhanced opportunities for work (SDG 1). However, there are some issues in human rights and inequality (SDG 8), greenhouse gas emissions (SDG 13), microclimate and soil nutrient changes (SDGs 6 and 13), sedimentation and hydrological changes (SDG 6), and human conflict with wildlife, invasive species, and reduced biodiversity (SDGs 14 and 15).…”
Section: Rspo Certification Contribution To Sdgs Achievementmentioning
confidence: 99%
“…al [26], also confirmed that oil palm plantation development activities offer additional benefits for sustainability related to socio-economic, environmental, and biodiversity [26]. To ensure the sustainability of oil palm development, several obstacles must be overcome to obtain measurable solutions such as the use of oil palm land that does not damage the environment as well as the participation and partnership of the government, companies, smallholders, and cooperatives [49].…”
Section: Factors Affecting the Nuclear Plasma Pattern Partnership In ...mentioning
confidence: 99%
“…Malaysia is now the second largest crude palm oil (CPO) producer after Indonesia, contributing 39% of world palm oil production and 44% of world exports [ 1 ]. Despite the fact that the palm oil industry contributed significantly to the Malaysian economy and improved the living standard of local society [ 2 ], the discharge of large amounts of oily wastewater from this industry remains the main concern to the public.…”
Section: Introductionmentioning
confidence: 99%